Comparison of efficacy of Retzius-sparing radical prostatectomy versus standard radical prostatectomy in the treatment of prostate cancer: a systematic review and meta-analysis - Gong, Weilun; Yan, Junfeng; Cui, Yilun; Zhang, Duojie; Ma, Yinfeng (Frontiers in Oncology, 2025)
ObjectiveTo compare the efficacy of Retzius-sparing robot-assisted radical prostatectomy (RS-RARP) versus standard robot-assisted radical prostatectomy (S-RARP) in treating prostate cancer patients regarding urinary continence (UC) recovery, oncological control, and other complications.MethodsAn electronic search was performed on four databases with no restrictions on the language up to May 16th, 2024. The main outcomes were UC recovery positive, positive surgical margin (PSM), biochemical recurrence (BCR) and postoperative complications. Result robustness was enhanced based on the RoB and quality assessments.ResultsThe final analysis included 3 randomized controlled trials, 2 prospective studies, and 4 retrospective studies. According to quantitative results, RS-RARP improved the UC recovery rates at catheter removal (OR=11.33, 95% CI=[1.29-99.69], P=0.03), at 1 month (OR=14.18, 95% CI=[1.34-150.44], P=0.03), 3 months (OR=3.64, 95% CI=[1.94-6.83], P<0.00001), 6 months (OR=3.18, 95% CI=[1.62-6.22], P=0.0007), but failed to present a better continence recovery rate at 12 months (OR=2.30, 95% CI=[0.77-6.85], P=0.14) postoperatively. The RS-RARP group presented higher overall PSM rates (OR=1.51, 95% CI=[1.15-1.98]) and PSM rates in ≥ pT3 tumors (OR=1.81, 95% CI=[1.18-2.77], P=0.006) versus the S-RARP group. Furthermore, the two groups did not present obviously different BCR rates (OR=0.58, 95% CI=[0.20-1.67], P=0.31), operating time (WMD=10.41 min, 95% CI=[-2.82-23.65], P=0.12), intraoperative estimated blood loss (WMD=-15.97 mL, 95% CI=[-41.53-9.58], P=0.22), serious postoperative complications (OR=1.04, 95% CI=[0.50-2.13], P=0.10).ConclusionsOur meta-analysis revealed that although RS-RARP demonstrated accelerated urinary continence recovery, it showed a tendency toward higher PSM rates in patients with ≥pT3 tumors.